2023
DOI: 10.2147/pgpm.s406644
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis and Experimental Verification of Immune Cell Infiltration and the Related Core Genes in Ulcerative Colitis

Abstract: Background Ulcerative colitis is a recurrent autoimmune disease. At present, the pathogenesis of UC is not completely clear. Hence, the etiology and underlying molecular mechanism need to be further investigated. Methods Three sets of microarray datasets were included from the Gene Expression Omnibus database. The differentially expressed genes in two sets of datasets were analyzed using the R software, and the core genes of UC were screened using machine learning. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In a study of colon cancer, it was found that inhibition of HMGCS2 increased glycolysis and decreased fatty acid βoxidation in colon cancer cells (Kim et al, 2023). In a previous integrated bioinformatics analysis study, HMGCS2 was found to be a relevant gene in the development of UC, which may be associated with the in ltration of neutrophils, monocytes and macrophages (Li et al, 2022;Zhao et al, 2023). Compared with normal tissues, HMGCS2 expression level was inhibited in the intestinal epithelium of UC patients in active phase (Kim et al, 2021), but its role in remission phase has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of colon cancer, it was found that inhibition of HMGCS2 increased glycolysis and decreased fatty acid βoxidation in colon cancer cells (Kim et al, 2023). In a previous integrated bioinformatics analysis study, HMGCS2 was found to be a relevant gene in the development of UC, which may be associated with the in ltration of neutrophils, monocytes and macrophages (Li et al, 2022;Zhao et al, 2023). Compared with normal tissues, HMGCS2 expression level was inhibited in the intestinal epithelium of UC patients in active phase (Kim et al, 2021), but its role in remission phase has not been studied.…”
Section: Introductionmentioning
confidence: 99%